Introduction: "Renegotiating Social Citizenship - Democracy in Welfare Service States" - Hans-Uwe Otto (Social Work and Society)
The assumption that welfare arrangements in Western societies develop towards Welfare Service States is increasingly discussed. Those Welfare Service States are characterized by personalized social services that have stepped out of their marginal position within welfare architectures to become a central pillar in welfare production. This has enormous structural, organizational and personnel consequences and leads to a fundamental restructuring of welfare policy program. These far-reaching changes in welfare state activities are reflected, for example, in a recognizable shift towards social-investment measures in the context of demographic, social and economic developments. Against this background, a democratically meaningful change in the relationship between citizens and the state becomes evident: A renegotiation of social citizenship is taking place.